Guided Laparoscopic Video Tutorials for Medical Student Instruction in Abdominal Anatomy - Dylan Isaacson (Association of American Medical Colleges, 2017)
Introduction As technological advances present new forms of media to anatomy educators involved in medical education, there is opportunity to expand on traditional dissection of embalmed cadavers. At the University of California, San Francisco School of Medicine, the surgery and anatomy departments collaborated to create guided video tutorials using laparoscopic surgical footage to teach the anatomy of the lesser sac and gastroesophageal junction. Methods These tutorials are instructional adjuncts to a laparoscopy session on fresh cadavers with first-year medical students. Students view the videos on their own before attending the anatomy lab. The anatomy lab includes six 30-minute sessions, in which approximately 22 students at a time leave their cadaver lab to participate in this laparoscopy session taught by colorectal surgeons and general surgery residents. Results Learner interest and satisfaction was measured through a postsession survey. Nearly all respondents indicated that the videos helped them learn the anatomy of the gastroesophageal junction and lesser sac, and were a valuable addition to dissection of embalmed cadavers. A second session was conducted with first-year medical students in which a pretest and posttest were administered before and after a screening of the tutorial on the gastroesophageal junction. Learners’ average scores on the test improved from 39% to 88% after watching the video. Discussion These data indicate that learners appreciate the incorporation of laparoscopy and video tutorials into anatomy education. These data further corroborate the measures of student enthusiasm, and support the value of the tutorials in short-term acquisition of anatomic knowledge.